Hepatitis delta virus facilitates the selection of hepatitis B virus mutants in vivo and functionally impacts on their replicative capacity in vitro. (January 2016) - Shirvani-Dastgerdi, E.; Pourkarim, M.R.; Herbers, U.; Amini-Bavil-Olyaee, S.; Yagmur, E.; Alavian, S.M.; Trautwein, C.; Tacke, F.
Abstract: To identify molecular interactions between hepatitis B virus (HBV) and hepatitis delta virus (HDV), HBV sequences were analysed in HBV/HDV-infected patients. Characteristic amino acid substitutions were found in cytosolic domains of hepatitis B surface antigen (HBsAg), in contrast to HBV-mono-infected controls. The functional impact of HDV on the replication of wild-type and mutant HBV was assessed in vitro . HDV co-transfection significantly reduced the replication of HBV strains containing precore or basal core promoter mutations, and HBV polymerase or surface antigen mutants affected HDV replication in vitro . Conclusively, our study revealed distinct HBsAg mutational patterns in HBV/HDV-infected patients and novel functional interactions between HBV and HDV.